2012
DOI: 10.1002/app.36763
|View full text |Cite
|
Sign up to set email alerts
|

Molecular network development and evolution of nanoscale morphology in an epoxy‐amine thermoset polymer

Abstract: Epoxy‐amine thermoset polymers exhibit a complicated, highly crosslinked network structure. The connectivity of this network drives material parameters such as mechanical properties and solvent permeation. Understanding the molecular network architecture is also an important aspect of the developing realistic network topologies for use in molecular dynamic simulations. Here, the evolution of network connectivity in a typical crosslinked epoxy‐amine network (Epon 828/3‐aminophenyl sulfone) is monitored as a fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 55 publications
3
21
0
Order By: Relevance
“…It is, on the other hand, well established that nanoscale fluctuations in cross-linking density do occur within thermoset epoxy resins. [33][34][35] Furthermore, we have previously shown that short term water uptake into model epoxy-phenolic resins is indeed heterogeneous at the nanoscale, and corresponds to slight variations in the degree of cross-linking density, in keeping with the Nguyen model. [16] Since water has been shown to diffuse through the intact coatings rapidly, it is feasible that the distribution of free-volume voids provided by these fluctuations in cross-link density provide favourable diffusive pathways through the coating.…”
Section: Discussionsupporting
confidence: 72%
“…It is, on the other hand, well established that nanoscale fluctuations in cross-linking density do occur within thermoset epoxy resins. [33][34][35] Furthermore, we have previously shown that short term water uptake into model epoxy-phenolic resins is indeed heterogeneous at the nanoscale, and corresponds to slight variations in the degree of cross-linking density, in keeping with the Nguyen model. [16] Since water has been shown to diffuse through the intact coatings rapidly, it is feasible that the distribution of free-volume voids provided by these fluctuations in cross-link density provide favourable diffusive pathways through the coating.…”
Section: Discussionsupporting
confidence: 72%
“…Previously, we conducted nanoindentation studies in order to understand the influence of the viscoelastic nature of the polymer on the resulting fracture surface. 27 These studies demonstrated that the observed nodular morphology is indeed a function of the underlying network structure rather than an artifact of some viscoelastic effect. This prior work indicates that the AFM images shown in Figure 6 highlight regions of relatively higher cross-link density that were left at the fracture surface as the propagating crack tip deviated to follow the lowest energy fracture pathway through regions with relatively lower cross-link density.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…28 More recently, examination of fracture surfaces has become possible under ambient conditions (i.e., circumventing any sample preparation effects) using the atomic force microscope (AFM), and numerous reports have emerged of nodular morphologies detected in tapping mode height or phase images. 26,29,30,31 However, Duchet et al countered that such features may be attributed to imaging artefacts generated by a blunt SPM probe tip scanning over rough surfaces, and a similar argument has recently been made for peakforce tapping mode modulus maps showing an apparently heterogeneous nanostructure for epoxy amine fracture surfaces. 32,33 These differences in interpretation are unsurprising, given that the evidence for heterogeneous network formation has largely been limited to topographical measurements of fracture interfaces.…”
Section: Insights Into Epoxy Network Nanostructural Heterogeneity Usimentioning
confidence: 91%